Fungibility and bandwagon effects of capital transfers in a federal context - Jaime Vallés-Giménez; Anabel Zárate-Marco (Kiel Institute for the World Economy (IfW), 2017)
The authors quantify the fungibility effect or diversion of resources towards purposes other than investment, by regions receiving conditional capital transfers. To identify this behaviour, they have taken different empirical approaches with frontier techniques that let them quantify whether the regions are investing the maximum available funds, given certain environmental factors. The results show that Spanish regions divert hardly any of their potential investments, and that the most prosperous regions are the ones that let the most resources leak into other uses, especially in economic boom periods. In contrast, in some poor regions the authors can identify the opposite phenomenon, in which resources are dragged along towards investment (bandwagon effect). They identified several factors explaining the fungibility effect: political aspects, poor management or planning associated with the accumulated debt, the political cost of tax collection, and other variables such as the level of economic development, population density, and the economic cycle.
Keywords: H20; H54; H7; 330; capital transfers; regional capital expenditure; fungibility effect; bandwagon effect; frontier techniques